2006
DOI: 10.1002/pssa.200521139
|View full text |Cite
|
Sign up to set email alerts
|

TL and PL in BaSr(SO4)2:Eu mixed sulphate

Abstract: A highly sensitive thermoluminescent (TL) phosphor based on BaSr(SO 4 ) 2 : Eu has been developed. The phosphor was recrystallized from H 2 SO 4 solution by evaporation. Photoluminescence studies of this mixed-sulphate phosphor show that Eu is incorporated in the host in its divalent (emission at 383 nm) as well as trivalent (emissions at 575 and 731 nm) form due to 4f 6 5d → 8 S 7/2 and 5 D 0 → 7 F j transitions, respectively. The intensity of the 383 nm band increases with increasing irradiation, while that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…al. [9] for g-ray irradiation. They found a prominent TL glow peak at 470 K along with small shoulder at around 428 K. Hence, there is no one-to-one correspondence in the position of the peaks in both the cases.…”
Section: Glow Curve Deconvolution By Glowfitmentioning
confidence: 99%
See 1 more Smart Citation
“…al. [9] for g-ray irradiation. They found a prominent TL glow peak at 470 K along with small shoulder at around 428 K. Hence, there is no one-to-one correspondence in the position of the peaks in both the cases.…”
Section: Glow Curve Deconvolution By Glowfitmentioning
confidence: 99%
“…It has been reported that mixed sulphate phosphors have well-desired characteristics like a high-temperature glow peak, linear response with ionizing radiation exposure, low fading and an easy method of preparation. Salah et al [9] explained that TL sensitivity of BaSr(SO 4 ) 2 :Eu is several times higher than that of the Ba and Sr sulphates. They also found that the optimum concentration of Eu is at 0.1 mol %.…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that mixed sulfate phosphors have well-desired characteristics like a high-temperature glow peak, linear dose response with ionizing radiation, low fading and an easy method of preparation [7][8][9]. Salah et al [10] have shown that TL sensitivity of BaSr(SO 4 ) 2 :Eu is several times higher than that of the Ba and Sr sulfates. They also found that the optimum concentration of Eu is 0.1 mol%.…”
Section: Introductionmentioning
confidence: 98%
“…It has been found that composite sulfates establish a type of TL phosphorus with better execution. For example, K2Ca2 (SO4)2: Eu [26], K3Na (SO4)2: Eu [27], Ba0 .97Ca0.03SO4: Eu [28], BaSrSO4: Eu [29] and K2Ca2(SO4)2: Eu, K2Ca2(SO4)2: Eu, Dy [30] is considered an exceptionally subtle TLD phosphorus. Dysprosium sesquioxide, Dy2O3 is a basic highly insoluble and thermally stable material [31].…”
Section: Introductionmentioning
confidence: 99%